2018
DOI: 10.1002/anie.201803396
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Driven Reverse Water‐Gas Shift at Ambient Conditions mediated by a Nickel Pincer Complex

Abstract: The endothermic reverse water-gas shift reaction (rWGS) for direct CO hydrogenation to CO is an attractive approach to carbon utilization. However, direct CO hydrogenation with molecular catalysts generally gives formic acid instead of CO as a result of the selectivity of CO insertion into M-H bonds. Based on the photochemical inversion of this selectivity, several synthetic pathways are presented for CO selective CO reduction with a nickel pincer platform including the first example of a photodriven rWGS cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Bearing in mind that not many Ni II ‐CO complexes are known to date, [25, 28–39] due to the limited ability of Ni II to stabilize such entities via backbonding, we next tested whether a Ni II ‐CO complex with the L t Bu− ligand system would be stable at all and reacted the cationic complex [L t Bu Ni II (OH 2 )][B(Ar F ) 4 ] ( 2 , see S3) with CO gas. A change of color from green to purple could be observed, and evaporation of all volatiles left behind a purple solid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bearing in mind that not many Ni II ‐CO complexes are known to date, [25, 28–39] due to the limited ability of Ni II to stabilize such entities via backbonding, we next tested whether a Ni II ‐CO complex with the L t Bu− ligand system would be stable at all and reacted the cationic complex [L t Bu Ni II (OH 2 )][B(Ar F ) 4 ] ( 2 , see S3) with CO gas. A change of color from green to purple could be observed, and evaporation of all volatiles left behind a purple solid.…”
Section: Resultsmentioning
confidence: 99%
“…Bearing in mind that not many Ni II -CO complexes are known to date, [25,[28][29][30][31][32][33][34][35][36][37][38][39] due to the limited ability of Ni II to stabilize such entities via backbonding,w en ext tested whether aN i II -CO complex with the L tBuÀ ligand system would be stable at all and reacted the cationic complex (Figure 2). Thestructure determination further revealed that one of the aryl rings of L tBu undergoes an h 2 coordination, thus completing as quare planar coordination sphere of the Ni center,w hich also reflects in ad iamagnetic 1 HNMR spectrum of as olution of 3 in CD 2 Cl 2 .…”
Section: à -Liberation Of Comentioning
confidence: 99%
“…Thermolcatalytic CO 2 conversion to hydrocarbons typically involves two pathways: the modified FT and methanol‐ and DME‐mediated synthesis routes, which are distinguished by their intermediates. The modified FT synthesis comprises CO 2 hydrogenation to CO intermediates via the reverse water‐gas shift (RWGS) reaction [Equation ()], [ 50 ] followed by CO hydrogenation to hydrocarbons via FT synthesis [Equation ()]. [ 1,51 ] The methanol and DME‐mediated synthesis routes are composed of CO 2 conversion to methanol and DME intermediates that further undergo methanol‐ and DME‐to‐hydrocarbon processes [ 52 ] CO2 + H2CO + H2O, ΔH25 °C=41.2 kJ mol1 nCO + 2nH2CnH2n + nH2O …”
Section: Co2 Conversion Over Zeolite‐based Catalystsmentioning
confidence: 99%
“…Similarities and differences between the two proposed catalytic systems for CO hydrogenation can be found in Scheme 57; it is possible to observe how the method proposed by Beller is superior in terms of hydrogen pressure, catalyst loading, as well as reaction time. In 2018, Schneider proposed a reverse water-gas-shift reaction (WGS) promoted by a nickel pincer complex at ambient reaction conditions [617]. The authors proposed a novel mechanism for In 2018, Schneider proposed a reverse water-gas-shift reaction (WGS) promoted by a nickel pincer complex at ambient reaction conditions [617].…”
Section: Co 2 Hydrogenation To Methanolmentioning
confidence: 99%